IJCM_412A: Self Medication Practices Among Patient Attending Fever Opd At Tertiary Care Hospital In Mumbai. - Miranda Roshni; Jakkula Shreekanth; Akankshamaravi (Wolters Kluwer Medknow Publications, 2024)
Background: Self-medication is defined as the use of drugs to treat self- diagnosed disorders or symptoms, or the intermittent or continued use of a prescribed drug for chronic or recurrent disease or symptoms. The practice of self-medication is common worldwide in both developed and developing countries which often leads to dangerous unwarranted adverse effects, antimicrobial resistance, ultimately increasing cost burden due to health care. Objective: The study aimed to determine the prevalence of self-medication among patients; to identify risk factors that could influence self-medication practices; to identify sources of information about medications used; and to identify reasons for self-medication. Methodology: cross-sectional study was carried out among patient, information regarding self-medication use in the past six months and associated sociodemographic factors, purpose, source of drug procurement, attitude toward self-medication use were collected. The data were obtained using a validated pretested self-administered questionnaire. The collected data will be analyzed using SPSS for descriptive and inferential statistics. Results: In our study the prevalence of Self Medication practices were observed to be 45.6%. The practice was noticed more among individuals from lower middle class family with a prevalence rate of 26%. Telling the symptoms to pharmacist was the commonest method adopted to procure drugs by the users i.e. 61%Majority of the self-medication users expressed that self-medication is harmless and 32.2 % found it effective and 88.9% said they had never experienced any adverse effects, 81.3 % consider it as acceptable practice. Conclusion: Prevalence of SM practices are high. Most common reason being poverty, confidence in self - diagnosis, In order to mitigate the negative effects of SM behaviours, additional prompt measures are required.